Enhanced recovery programs in gastrointestinal surgery: Actions to promote optimal perioperative nutritional and metabolic care - Gianotti, Luca; Sandini, Marta; Romagnoli, Stefano; Carli, Franco; Ljungqvist, Olle (Clinical nutrition, 2020)
The enhanced recovery after surgery (ERAS) pathway is an evidence-based approach to the use of care elements along the patient perioperative pathway. All care elements that may impact on clinically relevant outcomes have been considered and reviewed. The combined ERAS actions allow a quicker return to bowel function, oral feeding, nutritional and metabolic equilibrium, normal activity and ultimately to achieve better outcomes. Because of the multi factorial approach and the commitment of all the professionals caring for the patient, it is necessary to have the engagement of all disciplines, such as surgery, anesthesiology, clinical nutrition, nursing, physiatry, involved. ERAS is a dynamic process and new evidence are constantly integrated into the program. The primary endpoint of this review is to give updated information on the key ERAS actions to achieve optimal perioperative nutritional and metabolic care.
Available online 25 October 2019
Gesehen am 28.04.2020